Pharmacokinetics and Toxicity of Oral (-)-(S)-Bromofosfamide in Lung Cancer Patients - Kobylińska, Kamila; Koralewski, Piotr; Sobik, Barbara; Gąsiorek, Małgorzata; Kobylińska, Maria (Arzneimittelforschung, 2001)
The pharmacokinetics and toxicity of (-)-(S)-bromofosfamide ((2S)-(2-chloroethyl-amino)-3-(2-bromoethyl)-1,3,2-oxaza-phosphorinae 2-oxide, CAS 146452-37-1, CBM-11) were determined in ten patients with non-small cell lung cancer following an oral dose of 1.38 g/m2 B.S.A. (Body Surface Area). The drug was given as a powder in gelatine capsules to fasting patients. Plasma samples were collected during the first 24 h after administration. All samples, after extraction with chloroform, were assayed by a reverse phase HPLC method using UV detection at 200 nm. Orally administered (-)-(S)-bromofosfamide showed relatively fast absorption kinetics. Peak concentration of 47 μg/ml was observed after 1 h. The average half-life was about 5 h. Toxicities associated with oral (-)-(S)-bromofosf-amide therapy consisted of symptoms regarding the central nervous system, gastrointestinal tract and urinary tract. Neurotoxic symptoms were the most common clinically significant side effects and probably dose limiting.
Keywords: Bromofosfamide, clinical pharmacokinetics, toxicity; CAS 146452-37-1; CBM-11; Cytostatics; Non-small cell lung cancer